2022
DOI: 10.1108/jacpr-03-2022-0701
|View full text |Cite
|
Sign up to set email alerts
|

Effect of educational intervention based on theory of planned behavior on aggression preventive behaviors in students

Abstract: Purpose Aggressive behaviors are common among students. Given the importance of education in reducing aggressive behavior, this study aims to examine the influence of a theory of planned behavior (TPB)-based educational intervention on aggression-preventive behaviors in fifth-grade male students in Fasa city, Iran. Design/methodology/approach A total of 120 male students were randomly picked from several public schools in Fasa city, Iran, between 2018 and 2019. Assessments were completed before and three mon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 24 publications
1
2
0
Order By: Relevance
“…However, there was no significant difference in the control group. This finding is consistent in line with several studies on young adults and adolescents that show that educational intervention programs have increased the individual's knowledge in the experimental group [59,60], also, corroborated the findings of Khaleghi et al [61].…”
Section: Discussionsupporting
confidence: 92%
“…However, there was no significant difference in the control group. This finding is consistent in line with several studies on young adults and adolescents that show that educational intervention programs have increased the individual's knowledge in the experimental group [59,60], also, corroborated the findings of Khaleghi et al [61].…”
Section: Discussionsupporting
confidence: 92%
“…Adolescents who have more control over aggressive behavior are less likely to engage in such behavior and maintain a safe traffic order on their rides. Educational intervention is an effective measure to prevent aggressive behavior [ 75 ].…”
Section: Discussionmentioning
confidence: 99%
“…According to Bandura, knowledge of the dangers and benefits of behavior is a precondition for changing behavior, and if people lack awareness in this regard, there is not enough reasons to tolerate problems associated with changing the previous behavior [21]. The results of study indicated demonstrated that all the constructs of TPB have predictive power of aggressive behavior, but perceived behavioral control construct has significantly higher predictive power for predicting aggression intention and behavior [22].…”
Section: Determining Of Predictive Power Of Constructs Of Tpb To Cont...mentioning
confidence: 98%